2007
DOI: 10.1111/j.1939-1676.2007.tb02921.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features and Outcome Predictors of Leptospira interrogans Australis Serogroup Infection in Dogs: A Retrospective Study of 20 Cases (2001–2004)

Abstract: Background and Hypothesis: We retrospectively evaluated the clinicopathologic findings and outcome predictors in dogs with Leptospira interrogans Australis serogroup infections.Animals and Methods: The medical records of 159 dogs that had a leptospiral microscopic agglutination test (MAT) performed between 2001 and 2004 were reviewed.Results: Twenty dogs met serologic criteria for either symptomatic (16 dogs) or asymptomatic (4 dogs) infection caused by Leptospira interrogans Australis serogroup. Seven of 16 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(13 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…Clinical manifestations of canine leptospirosis are very similar to the human disease, including acute renal and hepatic failure, hemostatic disturbances, and an increase in pulmonary involvement over the last few years, closely resembling the severe pulmonary form of leptospirosis (SPFL) described in humans [23,31,41]. Severity of disease and organ involvement may vary, and current data do not support an association with the inciting serovar, although exact serovar identification based on culture and strain isolation have not been performed in these studies that were only based on serology results [36].…”
Section: Resultsmentioning
confidence: 99%
“…Clinical manifestations of canine leptospirosis are very similar to the human disease, including acute renal and hepatic failure, hemostatic disturbances, and an increase in pulmonary involvement over the last few years, closely resembling the severe pulmonary form of leptospirosis (SPFL) described in humans [23,31,41]. Severity of disease and organ involvement may vary, and current data do not support an association with the inciting serovar, although exact serovar identification based on culture and strain isolation have not been performed in these studies that were only based on serology results [36].…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that dogs may be an alternative maintenance host for the serovar Bratislava [ 23 ]. A seropositive reaction to the serogroup Australis has been associated with severe clinical disease in dogs [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Developing vasculitis can be the cause of mild ascites and hydrothorax, peripheral edema. Rarely ECG changes admitted in dogs (Mastrorilli et al, 2007), what can be explained by intracardial-vasculitis or inflammation.…”
Section: Discussionmentioning
confidence: 98%